2009
DOI: 10.1007/s12217-009-9170-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Magneto-Gravitational Environment on Silkworm Embryogenesis

Abstract: The objective of this research was to observe whether silkworm embryos can survive in a high magneto-gravitational environment (HMGE) and what significant phenotype changes can be produced. The hatching rate, hatching time, life span, growth velocity and cocoon weight of silkworm were measured after silkworm embryos were exposed to HMGE (0 g, 12 T; 1 g, 16 T; and 2 g, 12 T) for a period of time. Compared with the control group, 0 g exposure resulted in a lower hatching rate and a shorter life span. Statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The LG-HMF also affects various cellular processes and structures and impacts more than simple displacement of amyloplasts [18]. Our previous studies have demonstrated that diamagnetic levitation using superconducting magnets affect the morphology, cytoskeleton architecture, and function of bone cells (osteocytes, osteoblasts, and osteoclasts) [19]–[26] and the development of silkworm eggs [27]. High-gradient magnetic fields can directly affect human pre-osteoclast FLG29.1 cell survival and differentiation [26].…”
Section: Introductionmentioning
confidence: 99%
“…The LG-HMF also affects various cellular processes and structures and impacts more than simple displacement of amyloplasts [18]. Our previous studies have demonstrated that diamagnetic levitation using superconducting magnets affect the morphology, cytoskeleton architecture, and function of bone cells (osteocytes, osteoblasts, and osteoclasts) [19]–[26] and the development of silkworm eggs [27]. High-gradient magnetic fields can directly affect human pre-osteoclast FLG29.1 cell survival and differentiation [26].…”
Section: Introductionmentioning
confidence: 99%
“…Glade et al (2006) reported that the magnetic levitation inhibits microtubule selforganization, and they proposed that many space experiments could be carried out equally well on the ground using magnetic levitation. Studies in our lab showed that the HMGE affected osteoblast morphology, cytoskeleton related protein expression, adhesion to extracellular matrix proteins and the development of silkworm eggs (Hammer et al, 2009;Qian et al, 2008Qian et al, , 2009aTian et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…The author proposes that this type of physicochemical process, described at the microscopic level, is implied in living systems, explaining particularly their sensibility to weak external fields or the organizing processes that occur in the early stages of embryogenesis. Other recent studies on the effect of magnetic and electromagnetic fields or of the weightlessness on cells or microtubule solutions, works that propose biotechnological solutions based on microtubules, but also more general articles on self-organization, refer to these works on microtubule self-organization in vitro (Crawford-Young 2006; Galimberti et al 2006;Yang et al 2006;Roesner et al 2006;Kroupova et al 2007;Coleman et al 2007;Qian et al 2008;Coleman et al 2008;Yang et al 2008;Strasak et al 2009;Seo et al 2009;Qian et al 2009a, b;Sieberer et al 2009;Qian et al 2010;Tian et al 2010;Olson et al 2010;Johnson and Lam 2010;Moes et al 2011;Meng et al 2011;Ayodele et al 2011). Some still take the reaction-diffusion scenario for granted and the others accept the idea that weak external fields act similarly on microtubules in vitro and in vivo.…”
Section: The Question Of Microtubule Spatial Self-organizationmentioning
confidence: 99%